(untitled) (Journal of Social Sciences Review, 2022)
Many governments and international organizations in Pakistan have introduced various reforms to promote the justice system in the country, but their efforts have ended in vain. The justice system in Pakistan has not been able to provide justice to common citizens. The reforms were aimed at decreasing the time span trials usually take in Pakistan and minimizing the cost of litigation; however, the basic purpose of the justice system, that is, the dispensation of justice, has remained unfulfilled. The reforms strengthened judicial hierarchy, improved infrastructures, and amended certain procedural laws but did nothing to address the real issues that were hindering the deliverance of justice to the common people. The legal fraternity and international donor agencies, who were the forces behind these reforms, have been the defenders of the formal justice system in Pakistan for reasons that are many.